FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT MENABUNG MAHASISWA DI BANK SYARIAH (Studi Empiris Pada Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Pattimura) - Layn, Yuyun Yuniarti; Kasben, Afida Firya (POLITEKNIK LP3I JAKARTA, 2023)
Factors that encourage millennials to be interested in saving at Islamic banks are education or knowledge, social environment, and level of religiosity. Knowledge is a foundation that fortifies individuals with different knowledge; only some have the same knowledge about Islamic banks. Therefore, this study aims to analyze the factors that influence students' interest in saving at Islamic banks, using qualitative and quantitative research methods, with the sampling technique being purposive sampling. The results showed that Islamic banking knowledge, social environment, and religiosity significantly affected students' interest in saving at Islamic banks.Keywords: Islamic Bank, Social Environment, Interest In Saving, Knowledge, Level Of Religiosity